2016
DOI: 10.47605/tapro.v8i1.210
|View full text |Cite
|
Sign up to set email alerts
|

FEEDING HABITS OF PACK LIVING DHOLE (Cuon alpinus) IN A DRY DECIDUOUS FOREST OF EAST JAVA, INDONESIA

Abstract: We conducted a study on the feeding habits of dholes in the Baluran National Park, Indonesia. Scat analysis was employed to identify the prey consumed. In total, 54 scats were collected across the park during the dry season of 2013 and analyzed to identify the prey of this species; at least 20 prey species were identified. Ungulates are the most important prey, estimated to contribute more than 95 % of the biomass consumed by dholes in BNP. Efforts to ensure availability of ungulates and to secure habitat will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…In Bhutan and Laos, Dholes were found to prey mostly on both medium and small-sized ungulates In Cambodia, although Dholes preferred Muntjac, a small-sized ungulate, they also regularly consumed Banteng (18% of diet), indicating Dholes are capable of sometimes preying on large-sized ungulates (Kamler et al 2020). Similary, in Baluran National Park, East Java, Dholes were found to consume mostly largesized ungulates including Banteng and Water Buffalo Bubalus bubalis (Nurvianto et al 2016). Thus, Dholes in Indonesia and other areas of southeastern Asia might be more likely to prey on large-sized ungulates compared to Dholes in India, where medium-sized ungulates are more common.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In Bhutan and Laos, Dholes were found to prey mostly on both medium and small-sized ungulates In Cambodia, although Dholes preferred Muntjac, a small-sized ungulate, they also regularly consumed Banteng (18% of diet), indicating Dholes are capable of sometimes preying on large-sized ungulates (Kamler et al 2020). Similary, in Baluran National Park, East Java, Dholes were found to consume mostly largesized ungulates including Banteng and Water Buffalo Bubalus bubalis (Nurvianto et al 2016). Thus, Dholes in Indonesia and other areas of southeastern Asia might be more likely to prey on large-sized ungulates compared to Dholes in India, where medium-sized ungulates are more common.…”
Section: Discussionmentioning
confidence: 83%
“…In summary, we provide the first photographic evidence of a predation on Banteng by Dholes. Although previous studies found that Dholes regularly consumed Banteng in Cambodia (Kamler et al 2020) and East Java (Nurvianto et al 2016), their predatory behavior towards Banteng had never been photographed. These photographs suggests that Dholes get in large packs to predate on Banteng and separate young from adults when attacking the young.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Both are nowadays endangered or critically endangered according to the IUCN red list of threatened species 1,2 . The African hunting dog, known also as painted dog, and the dhole are among the top predators in their respective habitats 3,4 thanks to the combination of several dental hypercarnivorous traits, skeletal adaptations to cursorial pack hunting and their highly developed social behaviour.The evolution of these hypercarnivorous canids is still unknown and open to debate 5,6 . Furthermore, there is also a great deal of confusion in the taxonomy of the extinct large-sized and hypercarnivorous canids, which use to be referred to different systematic denominations (see Supplementary Information).…”
mentioning
confidence: 99%
“…Both are nowadays endangered or critically endangered according to the IUCN red list of threatened species 1,2 . The African hunting dog, known also as painted dog, and the dhole are among the top predators in their respective habitats 3,4 thanks to the combination of several dental hypercarnivorous traits, skeletal adaptations to cursorial pack hunting and their highly developed social behaviour.…”
mentioning
confidence: 99%